Assessing the validity of two-dimensional video analysis for measuring lower limb joint angles during fencing lunge - Chida, K.; Inami, T.; Yamaguchi, S.; Nishioka, T.; Yoshida, Y.; Kohtake, N. (Frontiers in Sports and Active Living, 2024)
Introduction The fencing lunge (lunge), characterized by minimal body rotation, offers a movement well-suited for 2D video analysis. However, to the best of our knowledge, the validity of 2D video analysis for fencing has not been verified. This study aimed to validate 2D video analysis by comparing lower limb joints (hip, knee, and ankle joints) angles during lunge using both 2D video analysis and 3D motion analysis methods.